Geochemistry and tectonic setting of volcanic rocks in the Mahiroud volcano-plutonic complex, Southeast of Sarbisheh (Eastern Iran) - Sahar Benrashidiyan; Ahmad Ahmadi Khalaji; Peyman Eskandarnia; Shahriar Keshtgar; Zahra Tahmasbi (پترولوژی)
Introduction Mahiroud volcano-plutonic complex as an anticline (Lahnu-Mahiroud) forms a part of the Sistan suture zone (SiSuZ), and lies in the northern part of the Sistan suture zone (SiSuZ). According to Tirrul et al. (1983), the Mahiroud complex, which includes a series of metamorphosed intrusive and extrusive rocks, is related to the rifting of the ocean, and they also believe that the general nature of this complex is ophiolitic, but because layered gabbros and ultramafic rocks do not outcrop, this issue is not certain. Delavari et al. (2017) by studying the volcanic rocks of southern Gazik in the vicinity of the Mahiroud volcano-plutonic complex, believe these rocks belong to the magmatism of the island arc. Also, Keshtgar et al. (2019) studied the tonalitic stock of the Mahiroud volcano-plutonic complex and attributed these rocks to the environment above the subduction zones, especially the present-day island arc (IAT). The main purpose of the present study is to study and to determine the tectonomagmatism of the volcanic rocks of the Mahiroud volcano-plutonic complex. Regional Geology The oldest rocks of the studied area related to the ophiolitic and ultrabasic rocks of the Lower Cretaceous, and after that, the volcano-plutonic rocks of Mahiroud along with sandstone, limestone and shales of the Upper Cretaceous were exposed. The sequences of flysch sediments from Paleocene to Pliocene exist in this area, so that the Oligo-Miocene magmatism can also be seen in it. The largest outcrop of the Mahiroud complex is located in the southern part of this belt and consisting of two parts: (1) The western part, which mainly includes pillow lava, andesite, tuff, and conglomerate. (2) The eastern part, including a complex of sheeted dykes and diabase trending approximately north - south. Analytical Methods 50 samples of the rocks under study with the least amount of weathering and alteration were collected from which, 20 thin sections were prepared for microscopic studies. Among these samples, 11 samples were selected for ICP-MS geochemical analysis for minor elements and AF-01-Lithium Fusion for major elements at the Zarazma Laboratory in Tehran. GCDkit, Excel and Corel Draw software were used to check the chemical results. Petrography The rocks of the studied area include volcanic rocks ranging from andesite- basalt, basalt and diabase, crosscutting by a tonalitic stock of Upper Cretaceous (Keshtgar et al., 2019). The boundary between the sedimentary-volcanic units of this area is mainly fault type and is generally cut by two sets of strike-slip faults in the northwest and northeast directions. The texture of these volcanic rocks is amygdaloid and porphyry. Euhedral, subhedral or anhedral. plagioclase forms a high-volume percentage of these rocks, Also, anhedral and subhedral amphiboles with Carlsbad twins can be seen as micro and macro crystals. Small volume of subhedral. pyroxenes and anhedral alkali feldspars are present. Secondary minerals include sericite, chlorite, epidote, calcite and iron oxide (opaque mineral). Whole Rocks Chemistry The whole rock analysis results of the investigated volcanics show that these rocks are classified as andesite-basalt, subalkali basalt and dacite-rhyodacite, placed mostly in the range of tholeiite series (low potassium) of the volcanic arc. This volcanic group is related to the Raskoh volcanic arc of Pakistan. The (Tb/Yb)N values less than 1.8 of these samples indicate the depth of magma melting in the range of 80 km and less than that from a spinel peridotite source. Therefore, the volcanic rocks of Mahiroud area composed of spinel lherzolite melting and the depth is less than the stability field of garnet in the island arc. Discussion The Mahiroud rocks are related to orogenic and tholeiitic basalts of island arc. Compared to N-MORB, these rocks show enrichment in LILE and depletion of HFSE Enrichment in LILE is one of the characteristics of island arcs, which are formed due to the metasomatized of the subducted plate. Also, the Ce negative anomaly in these volcanic rocks is consistent with the characteristics of the island arc, which is the result of the formation of fluids caused by the melting and dewatering of the pelagic sediments of the subducting oceanic plate. The formation of these MORB-type in the subduction zones indicates the melting caused by the release of pressure and the rise of the mantle; It possibly related to the fracture of the thinned arc crust. Conclusion The volcanic rocks of Mahiroud volcanic-intrusive complex show a range of, andesite-basalt, subalkali basalt and dacite-rhyodacite. The texture of these volcanic rocks is amygdaloid and porphyry type and their constituent minerals are mainly plagioclase, amphibole, pyroxene, and quartz. The geochemical characteristics of the studied volcanics show that the parent magma is tholeiitic nature (low potassium) originated from the melting of spinel peridotite at a depth, lower than the stability field of garnet. In terms of tectonic setting, most of the samples ranging from volcanic arc basalts and are consistent with the samples of the Raskoh volcanic arc of Pakistan.